Relationship between Body Weight and Linear Body Measurements in Japanese Quail (Coturnix coturnix japonica) (Journal of Scientific Research, 2013)
A total of 108 two-weeks-old Japanese quail chicks were used to study the relationship between body weight and linear measurements and to predict body weight from linear measurements of body length (BL), body girth (BG), wing length (WL), shank length (SL), shank diameter (SD) and drum stick (DS).The results showed that the mean quail birds body weights were 35.23g and 143.78g, at 2nd and 8th weeks, respectively. Body weight gain was increased between 2 and 6 weeks of age and thereafter decreased with advancing age. Female birds were significantly (P< 0.05) heavier than those of male counterpart at 6th and 8th weeks of age. Significantly positive correlations (P